XELOX combined with sintilimab and hyperbaric oxygen therapy for advanced or metastatic gastric/gastroesophageal junction adenocarcinoma: study protocol for a prospective, single-arm, phase Ib/II clinical trial - Li, Wenke; Zhang, Pengfei; Cheng, Mo; Wei, Jing; Xu, Menghui; Li, Dan; Song, Sihui; Liu, Ming; Huang, Cheng; Zhu, Lin (Frontiers in Immunology, 2026)
BackgroundGastric and gastroesophageal junction cancer (GC/GEJC) is the fifth most common and deadliest cancers worldwide, with five-year survival rates ranging from 20–40% due to late-stage diagnosis. First-line treatment for HER2-negative advanced or metastatic GC/GEJC involves chemotherapy combined with PD-1 inhibitors, achieving an objective response rate (ORR) of approximately 60%. However, primary and acquired resistance limits effectiveness, highlighting the need for novel strategies. Tumor hypoxia reduces the efficacy of immune checkpoint inhibitors (ICIs). Hyperbaric oxygen therapy (HBOT) may alleviate hypoxia, enhance drug delivery, and improve immune cell infiltration, potentially increasing the antitumor effects of ICIs.MethodsThis prospective, single-center, single-arm phase Ib/II trial evaluated the efficacy and safety of the XELOX regimen combined with sintilimab and HBOT in HER2-negative advanced or metastatic GC/GEJC patients. Phase Ib employs a 3 + 3 dose-escalation design with nine patients to assess safety and determine the optimal HBOT protocol. Phase II will enrol 48 patients, accounting for a 5% dropout rate, with a focus on the ORR as the primary endpoint. The secondary endpoints include progression-free survival (PFS), the disease control rate (DCR), 2-year disease free survival (DFS), two-year overall survival (OS), quality of life (QoL), and safety. All participants received XELOX, sintilimab and HBOT. Efficacy is assessed every two cycles, with maintenance therapy continuing until disease progression or other termination criteria are met.DiscussionThis is the first clinical trial to explore the efficacy and safety of HBOT combined with chemotherapy and immunotherapy in HER2-negative advanced or metastatic GC/GEJC patients. These results may provide a novel treatment strategy for patients with advanced GC/GEJC, addressing the current limitations of immunotherapy resistance.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT06742411.